A Proposed Vision To Strengthen The Psychological And Social Support For Orphans In Care Homes - Deea Ahmed Alkurd (AL LUGHAH, 2021)
The study aimed to identify the necessity of building a proposed vision to enhance the psychological and social support of orphans in care homes, and the researcher reviews in this study the definition of the study terms represented in psychological and social support and orphanages and care homes, as well as the difficulties and challenges facing orphan care institutions in providing psychological and social support to orphans The researcher used the descriptive desktop approach to identify the literature related to developing the proposed vision to enhance psychological and social support for orphans in care homes. The study showed that providing psychological and social support helps orphans Depositors in care homes to face life stresses and positive adaptation to the circumstance of loss and overcome difficulties before them in order to develop their psychological and social compatibility, as well as enable them through programs to explore their capabilities and develop their capabilities and raise their competencies. The study recommended providing orphan care institutions with the amenities, entertainment and educational games aimed at contributing to creating a positive atmosphere aimed at achieving psychological and social compatibility for the orphans in which they are placed1. Ibrahim, Zakaria (1973 AD) The Artist and the Man, Egypt: Dar Gharib for Printing and Publishing.2. Istiti, Tasnim, Muhammad Jamal. Hassan (2007 CE): Orphan's Rights in Islamic Jurisprudence, Master Thesis, College of Graduate Studies, An-Najah National University, Nablus, Palestine.3. Al-Buraq, Amna (2011): The needs of adults of unknown parentage after leaving institutions for orphans, the first Saudi conference for orphan care.4. Jalal, Nusseibeh (2017): Psychological care for Syrian refugee orphans, "a field study", Research Center for Studies, Syria.5. Al-Halibi, Khalid bin Saud (1425 AH): How can you contribute to developing the positive character of an orphan by making use of educational experiences, a working paper in a symposium entitled: “Future visions for orphan care in the Kingdom of Saudi Arabia,” Ministry of Social Affairs, Ministry Agency For Social Affairs, Social Affairs Office, Dammam, Tuesday 21/8/1425 AH corresponding to 5/10/20046. Hamzah, Ahmad (2011): The Effectiveness of an Integrated Counseling Program in Reducing Violence for a Sample of Orphaned Delinquent Children, The First Saudi Conference for Orphan Care.7. Al-Khayyat, Abdul Aziz (1981): Interdependent Society in Islam, 2nd Edition, Al-Risalah Foundation, AmmanAl-Sadhan, Abdullah bin Nasser (2001); Children without families, Obeikan Library, Riyadh.9. Al-Sulami, Musleh Salih (1415 AH), raising orphans in the Kingdom of Saudi Arabia, an evaluation study, an unpublished master's thesis, Department of Islamic Education, College of Education, Umm Al-Qura University, Makkah Al-Mukarramah.10. Al-Suwairi, Ali Abdullah; (2009 AD); “Psychological and Social Problems among Orphans in the Charitable Society of Makkah Al-Mukarramah”, Master Thesis, College of Education, Department of Psychology, Umm Al-Qura University, Makkah Al-Mukarramah.11. Amer, Adel (2004 AD); Orphan children have no legal and legal protection, a study published (in :) The House of Legal, Islamic and Human Sciences Forum, http://adel-amer.catsh.12. Al-Anani, Hanan Abdel-Hamid (2005): Development of Social, Religious and Ethical Concepts in Early Childhood, Jordan: House of Fikr.13. Al-Matrafi, Fawzia Muhammad Abdel Mohsen; (2001): “Study of the relationship between the nutritional status and meals provided to children of orphanages in Makkah Al-Mukarramah region for school-age children (12-6 years old)”, PhD Thesis, College of Education for Home Economics, Department of Nutrition and Food Sciences, Makkah Al-Mukarramah.14. Al-Nuwaiser, Khalid bin Abdulaziz, (2011): The role of national systems in protecting and caring for orphans' rights, The First Saudi Conference for Orphan Care.15. Browne, K. (2009). The Risk of Harm to Young Children in Institutional Care. Typeset by Grasshopper Design Company. Printed by Stephen Austin & Sons Ltd.16. Carter R. (2005). Family Matters: A study of institutional childcare in Central and Eastern Europe and the Former Soviet Union. London:Everychild.